Maternal Anemia in Patients with Preterm Delivery in Indonesia - Mayangsari, Nastiti Hemas; Suhaimi, Donel (Faculty of Medicine, Universitas Padjadjaran, 2025)
Preterm delivery remains one of the leading causes of fetomaternal morbidity and mortality worldwide. Anemia during pregnancy is also a significant concern, and may contribute to adverse pregnancy outcomes including preterm birth, intrauterine growth restriction (IUGR), and postpartum hemorrhage (PPH). This study aimed to assess the prevalence of maternal anemia in women with preterm delivery and to evaluate its association with preterm-related complications. A retrospective cross-sectional study was conducted at the Obstetrics and Gynecology Department of Arifin Achmad Hospital, Pekanbaru, Indonesia. Anemia was defined according to the CDC criteria as hemoglobin levels below 11 g/dL in the first and third trimesters or below 10.5 g/dL in the second trimester. Data were collected from medical records of 654 preterm deliveries, of which 359 met the inclusion criteria. Among these, 204 women (56.82%) had anemia, while 155 women (43.18%) had normal hemoglobin levels. A significant association was found between anemia and preterm delivery (p=0.010). Maternal anemia was associated with preterm premature rupture of membranes (PPROM) (p=0.035, contingency coefficient=0.110, 95% CI). These findings suggest that maternal anemia is significantly correlated with preterm birth and its complications, particularly PPROM. Screening and early management of anemia in pregnancy may help reduce the risk of preterm delivery and improve maternal and neonatal outcomes.